Identificación de microorganismos edáficos asociados a cuatro diferentes plantaciones forestales en la zona central del Litoral Ecuatoriano. - Cruz Cruz, Adrián Alfredo (2015)
In this research the identification of soil microorganisms associated with four different forest plantations in the central area of the Ecuadorian coast was made, the work I consist of 4 treatments and 3 repetitions, the treatments studied were: T1: Forest Plantation Cybistax donnel -smithii (white Guayacán), T2: Forest Plantation Schizolobium parahybum (Pachaco), T3: forest plantation Terminalia ivorensis (Terminalia), T4: forest plantation Cordia alliodora (Laurel). Different methodologies for the identification of functional groups (bacteria and fungi) were used. Regarding the biochemical analysis Gram stain performed on all four study treatments, a greater number of gram positive and catalase positive four found commercial forest plantations. Regarding fungal populations count at 96 hours and 120 hours of inoculation statistically significant differences between treatments where T1 Cybistax donnel-smithii was superior to other treatments were presented. The populations of proteolytic bacteria from soil Cordia alliodora were higher than the other treatments with a value of 4,916 log10. The hypothesis at the beginning of this investigation, which is left for granted that bacterial and fungal as well as the functional groups of four commercial forest plantations, populations play a key role in soil was accepted.